Lactobacillus reuteri 1 Enhances Intestinal Epithelial Barrier Function and Alleviates the Inflammatory Response Induced by Enterotoxigenic Escherichia coli K88 via Suppressing the MLCK Signaling Pathway in IPEC-J2 Cells - Gao, Jingchun; Cao, Shuting; Xiao, Hao; Hu, Shenglan; Yao, Kang; Huang, Kaiyong; Jiang, Zongyong; Wang, Li (Frontiers in Immunology, 2022)
Intestinal epithelial barrier injury disrupts immune homeostasis and leads to many intestinal disorders. Lactobacillus reuteri (L. reuteri) strains can influence immune system development and intestinal function. However, the underlying mechanisms of L. reuteri LR1 regulate inflammatory response and intestinal integrity are still unknown. The present study aimed to determine the effects of LR1 on the ETEC K88 induced intestinal epithelial injury on the inflammatory response, intestinal epithelial barrier function and MLCK signal pathway and its underlying mechanism. Here we showed that the 1 × 109 cfu/mL LR1 treatment for 4h dramatically decreased the interleukin-8 (IL-8) and IL-6 expression. And then, the data indicated the 1 × 108 cfu/mL ETEC K88 treatment for 4h dramatically enhanced the IL-8, IL-6 and tumor necrosis factor-α (TNF-α) expression. Furthermore, scanning electron microscope (SEM) data indicated that pretreatment with LR1 inhibited the ETEC K88 adhered on IPEC-J2 and pretreated with LR1 alleviated the scratch injury of IPEC J2 cells. Moreover, LR1 pretreatment significantly reversed the declined trans-epithelium electrical resistance (TER), tight junction proteins level and enhanced induced by ETEC K88 treatment. Additionally, LR1 pretreatment dramatically declined the IL-8, IL-17a, IL-6 and TNF-α levels compared with ETEC K88 group. And then, ETEC K88 treated IPEC-J2 cells had a higher level of myosin light-chain kinase (MLCK), MLC levels and lower Rho-associated kinase (ROCK) level than the control group. While, LR1 pretreated significantly declined the MLCK, MLC expression and enhanced ROCK level in the ETEC K88 challenged IPEC-J2 cells. Mechanistically, depletion of MLCK significantly declined MLC expression in IPEC-J2 challenged with ETEC K88 than si NC+ ETEC K88 group. On the other hand, the TER of in si MLCK + ETEC K88 group was higher and the FD4 flux in si MLCK + ETEC K88 group was lower compared with the si NC +ETEC K88 group. In addition, depletion of MLCK significantly enhanced Claudin-1 level in IPEC-J2 pretreated with LR1 followed challenged with ETEC K88. In conclusion, our work indicated that L. reuteri LR1 can decline inflammatory response and improve intestinal epithelial barrier function through the suppressing MLCK signal pathway in the ETEC K88 challenged IPEC-J2.